1993
DOI: 10.2307/1166118
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Sex Typing in Middle Childhood

Abstract: The present study examined the development of sex typing during middle childhood, using a sample of 558 children aged 5-12 years. The purpose of the study was to provide information about the developmental course and stability of various aspects of sex typing during this period and to examine the relative contributions of cognitive and environmental factors to sex-role development. Multiple measures of sex typing were obtained, including indices of personal preference, knowledge of stereotypes, and flexibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
122
2
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(142 citation statements)
references
References 8 publications
16
122
2
2
Order By: Relevance
“…Although previous investigations, including longitudinal studies, have shown the same increase in stereotype flexibility after age 6 that we found in this study (e.g. Serbin et al, 1993), previous analyses have not considered the possibility that this growing flexibility is connected to an earlier period of rigidity in a fundamental, almost stage-like, way. The present findings show that children follow a very similar pattern of rigidity followed by flexibility, regardless of what age rigidity occurs and regardless of their level of peak rigidity.…”
Section: Discussionsupporting
confidence: 68%
“…Although previous investigations, including longitudinal studies, have shown the same increase in stereotype flexibility after age 6 that we found in this study (e.g. Serbin et al, 1993), previous analyses have not considered the possibility that this growing flexibility is connected to an earlier period of rigidity in a fundamental, almost stage-like, way. The present findings show that children follow a very similar pattern of rigidity followed by flexibility, regardless of what age rigidity occurs and regardless of their level of peak rigidity.…”
Section: Discussionsupporting
confidence: 68%
“…Serbin, Powlishta, and Gulko (1993) found flexibility and knowledge of gender stereotypes to be largely a function of the child's maturity level. They note, however, that sex-typed behaviour was modelled on what children observed by their parents.…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge of occupational gender stereotypes seems to be present in children as young as 3 years old and it tends to increase with age (e.g., Martin & Little, 1990); children also continue to aspire to gender-typed jobs (e.g., Etaugh & Liss, 1992;Sellers, Satcher, & Comas, 1999) towards which they have more positive affective reactions (Levy, Sadovsky, & Troseth, 2000). Serbin, Powlishta, and Gulko (1993) examined the development of gender-typing in a sample of children ages 5 to 12 years, using multiple measures of gender-typing, including indices of knowledge of stereotypes and flexibility in the domains of activities, occupations, and traits (cognitive elements) and indices of personal preference, such as gender-typed preferences for activities, occupations, and peers (affective elements). Their results supported the need for an integrative theory of sex-role development, incorporating factors emphasized by cognitive-developmental, schematic-processing, and social learning theories.…”
mentioning
confidence: 99%